Successful use of lower-level laser therapy in the treatment of medication-related osteonecrosis of the jaw - Momesso, Gustavo Antonio Correa [UNESP]; de Souza Batista, Fábio Roberto [UNESP]; de Sousa, Cecília Alves [UNESP]; de Lima, Valthierre Nunes [UNESP]; Polo, Tárik Ocon Braga [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP]; Faverani, Leonardo Perez [UNESP] (My University, 2017)
Case Presentation: This study aimed to report a case of medication related osteonecrosis of the jaw (MRONJ) of a 65-year-old female patient referred to the Oral and Maxillofacial Surgery team from Araçatuba Dental School, complaining about mobility of a previously dental implant placed on the posterior maxillary region. Clinical examination revealed an extensive necrosis area around the implant region. The patient reported bisphosphonate therapy with sodium alendronate for prevention of osteoporosis 5 years ago. A diagnosis of MRONJ was reached and the treatment decided was to remove the dental implant damaged and use the lower-level laser therapy (LLLT) associated with antibiotic therapy with clindamycin 300 mg and mouth rinses with chlorhexidine 0.12%. Conclusion: Six months after the treatment with LLLT a complete healing of the affected area was observed and 12 months after treatment the patient was rehabilitated with fixed dental prosthesis and showed excellent tissue healing of the necrosis areas. It was concluded that the use of LLLT showed to be a good option in the treatment of MRONJ.
Keywords: Antiresorptive drugs; Biphosphonates; Laser therapy; Osteonecrosis of the jaw